Towards modeling of human skilling for electrical circuitry using augmented reality applications - Villanueva, Ana; Liu, Ziyi; Kitaguchi, Yoshimasa; Zhu, Zhengzhe; Peppler, Kylie; Redick, Thomas; Ramani, Karthik (International Journal of Educational Technology in Higher Education, 2021)
Augmented reality (AR) is a unique, hands-on tool to deliver information. However, its educational value has been mainly demonstrated empirically so far. In this paper, we present a modeling approach to provide users with mastery of a skill, using AR learning content to implement an educational curriculum. We illustrate the potential of this approach by applying this to an important but pervasively misunderstood area of STEM learning, electrical circuitry. Unlike previous cognitive assessment models, we break down the area into microskills—the smallest segmentation of this knowledge—and concrete learning outcomes for each. This model empowers the user to perform a variety of tasks that are conducive to the acquisition of the skill. We also provide a classification of microskills and how to design them in an AR environment. Our results demonstrated that aligning the AR technology to specific learning objectives paves the way for high quality assessment, teaching, and learning.